Defending Sleepwalkers with Science and an Illustrative Case - Cartwright, Rosalind D. (American Academy of Sleep Medicine, 2013)
OBJECTIVE: To test whether laboratory-based research differentiating sleepwalkers (SW) from controls (C) can be applied in an uncontrolled forensic case as evidence the alleged crime was committed during an arousal from sleep in which the mind is not fully conscious due to a SW disorder. METHODS: A PSG study recorded 8 months after the defendant was charged was analyzed independently by spectral analysis. Slow wave activity (SWA) and cyclic alternating pattern (CAP) rates were computed. Clinical interviews and police records were reviewed for data re: the defendant's sleep prior to the event and use of drugs, alcohol, and stimulants. RESULTS: The SWA distribution was abnormally low and flat, significantly lower than published controls; in the first NREM cycle, CAP rate 55 was above normal. Two weeks of prior sleep deprivation was confirmed from interviews and defendant's observed daytime sleepiness. Caffeine intake the day before the event was calculated at 826 mg over 14 hours. Snoring and a mild breathing disorder were present in the PSG. CONCLUSION: Testimony based on spectral analysis of PSG recorded following an alleged criminal event supported a SW explanation for the non-rational behaviors charged. The defendant was acquitted of all charges and has been successfully treated. CITATION: Cartwright RD; Guilleminault C. Defending sleepwalkers with science and an illustrative case. J Clin Sleep Med 2013;9(7):721-726.